Answer:
x = -
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
Explanation:
Given
20x - 2 = 36x + 10 ( subtract 36x from both sides )
- 16x - 2 = 10 ( add 2 to both sides )
- 16x = 12 ( divide both sides by - 16 )
x =
= -
![(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/e14yosw5rbprbu04e78upb04bghif5atho.png)
As a check
Substitute this value into the equation and if both sides are equal then it is the solution.
left side = 20 × -
- 2 = - 15 - 2 = - 17
right side = 36 × -
+ 10 = - 27 + 10 = - x17
Since both sides are equal then x = -
is the solution